Pieśni ku czci Trójcy Przenajświętszej w ”Śpiewniku archidiecezji katowickiej” - Hudek, Wiesław (Studia Pastoralne, 2018)
The Book of Songs of Katowice Archdiocese, published in 2000 by Rev. Professor Antoni Reginek, contains 9 songs of praise to the Holy Trinity in the collection in which they are numbered from 197 to 205. Compared with other collections of church songs, it is placed as the second in row as far as the quantity of such works is concerned. The biggest collection of songs of praise to the Holy Trinity is the Evangelical Book of Songs (Bielsko-Biała 2002) with a number of eleven songs. Following The Book of Songs of Katowice Archdiocese is the book The Way to Heaven (Droga do nieba, Opole 2006) with six songs and The Hymn Book by Rev. Jan Siedlecki (Kraków 2017) with five songs of praise to the Holy Trinity. The texts of the analyzed songs can be divided into three formal genres: antiphonies, hymns, and stanza songs. Their content is bound up by descriptions of the nature of the Holy Trinity (Divinity and Unity), internal relations (creation, origin, and inspiration) and the external action (creation, salvation and devotion). The language of the songs is rich with metaphors and poetics that approximates the mystery of God. Musically, the songs are characterized by the noble simplicity. The melody in majority of them is held in key major and in two cases one can find references to church modes. Four are held in 4/4 meter, and two in duple meter, which reinforces the musical illustration of the Holy Trinity mystery. The ambitus of the songs accommodates to the average human voice capacity and varies from the largest one containing the eleventh (203) to the smallest one in the interval of the sixth (199, 202). The examples of particularly vital songs can be: the Silesian Hymn Te Deum Laudamus or We praise you God (199) and the song The Undivided and Holy Trinity (202). This hymn is known and sung in all parishes of the archdiocese (paradoxically in all churches it is sung in the meter different from 3/4). The second song, apart from the melodic variation placed in the collection (counter-facture to the morning song When the morning stars are awake [549] and the evening hymn All our daily matters [553]) has its original version which functions in the living musical tradition in the Silesian Chełm parish.